PENGARUH KINERJA MALL PELAYANAN PUBLIK (MPP) TERHADAP KUALITAS PELAYANAN PEMERINTAH KABUPATEN TULANG BAWANG - Nika Mareta Ramadani; Budhi Waskito; Agustuti Handayani (Universitas Bandar Lampung (UBL), 2020)
The problem formulation in this research is, (1) How the performance of the Mall Public Service in the government of Tulang Bawang regency. (2) How is the quality of service in Tulang Bawang Regency government. (3) How big the performance of public service Mall is to the quality of government services of Tulang Bawang District. This research uses the explanatory method of survey, by analyzing the effect of performance variables of public service Mall as a free variable (independent variable) to the quality of service as a dependent variable. Researchers use a research approach in accordance with the objectives that you want to achieve namely in addition to describing and describing empirical facts found in the field, will also perform inferential analysis between free variables and bound variables. The results of the research is the performance of Mall Public Service on the government of Tulang Bawang District has been running, but not optimal, it is because it has not been supported by the educational level of apparatus that has not been done, quality service Mall service Public at Tulang Bawang Regency Government, indicating that the variable quality service Mall public service has not been implemented as expected. Performance effect of public service Mall on the quality of government services of Tulang Bawang Regency, according to the results showed that the performance of the public Service Mall has a strong enough relationship of 64.2 percent against Quality of service, while the rest, 35.8 percent influenced by other factors that the author has not researched, thereby that the results of the study showed the significant influence of the performance of Mall Public Service (MPP) on quality Service on quality of service at the public Service Mall of Tulang Bawang Regency.